Quadruple labelled dual oxygen and pH-sensitive ratiometric nanosensors - Chauhan, Veeren M.; Giuntini, Francesca; Aylott, Jonathan W. (Elsevier, 2016)
Nanosensors capable of simultaneously measuring dissolved oxygen concentrations from 0 to 100% saturation and pH over the full physiological range, from pH 3.5 to 7.5, that advance the methods towards understanding of key biological gradients, were synthesised. A library of water soluble oxygen-sensitive porphyrins, with three substituted charged functional groups and a chemically flexible carboxylate functional group were spectroscopically analysed to assess their sensitivity to changes in dissolved oxygen concentrations as free species in solution and in suspension as nanoparticle conjugates. A platinum cationic porphyrin was taken forward to fabricate ratiometric oxygen-sensitive nanosensors, using 5-(and-6)-carboxytetramethylrhodamine (TAMRA) as internal standard. In addition, quadruple labelled dual oxygen and pH-sensitive nanosensors were synthesised using the cationic Pt porphyrin, pH-sensitive fluorescein dyes, carboxyfluorescein (FAM) and Oregon Green (OG), in a 1:1 ratio, and TAMRA. We envisage the dual oxygen and pH nanosensors will find broad utility in the characterisation of diverse microenvironments, where there are complex interactions between molecular oxygen and pH.